Evaluation of Sustainable Development Goals (SDGs) Indicators in Wantilan, Subang Regency, 2021 - Faishal Mahdy, Ilham; ., Abdul Kudus; Agustin Nuriani Sirodj, Dwi; Fauzi, Fachrul; Putri, Evania; Suliadi, Suliadi; Azizah Komara Rifai, Nur (KnE Social Sciences, 2023)
Sustainable development goals (SDGs) are a global agenda as the successor of the millennium development goals (SDGs) with a broader, holistic, and universal vision. The SDGs contain 17 goals, 169 targets, and 289 indicators which are used as a reference for local governments in developing their territories. In measuring success at the rural level, a categorization is used in the form of the Indeks Desa Membangun (IDM), which is formed based on three indices, namely, the social resilience index, the economic resilience index, and the ecological or environmental index. Wantilan is one of the villages with IDM status as a developed village located in Subang Regency. The status of the IDM needs to be upgraded to become an independent village by taking into account local government policies that are also related to the SDGs indicators. In addition, the condition of Wantilan Village which experienced a transition from being an agricultural area to an industrial area requires an evaluation of the achievement of the SDGs indicators. There are 4 areas of discussion related to SDGs available on the Wantilan Village Dashboard, including employment and education. The results of this study indicate that the achievement of certain SDGs indicators, especially in the fields of education and employment, has not met the expected targets. Keywords: achievement, IDM, rural, SDGs, Wantilan